Single-Phase Rectifier with Cascaded-Transformer to Supply a Three-Phase Induction Motor with Open-End Windings - Antônio D. D. Almeida; Bruna S. Gehrke; Nady Rocha; Edgard L. L. Fabricio; Carolina A. Caldeira; Gleice M. S. Rodrigues; Isaac S. de Freitas (Eletrônica de Potência)
This paper presents a single-phase to three-phase AC-DC-AC step-down converter with a symmetrical DC-link voltage ratio. The proposed converter architecture is well-suited for rural distribution grid applications, where a high-voltage single-phase grid is required to transmit energy over long distances while minimizing conduction losses. The converter consists of two cascaded H-bridge converters connected via transformers and two three-phase inverters supplying an open-end winding induction motor (OEWIM). The level-shifted pulse-width modulation (LSPWM) strategy is employed to synthesize the converter voltages. A proportional-integral (PI) controller regulates the overall DC-link voltages, while a hysteresis controller maintains the balance of the individual DC-link voltages. Additionally, a resonant PI controller ensures a sinusoidal grid current, and a Phase-Locked Loop (PLL) is used to achieve a high power factor in the grid. Compared to a conventional two-level leg topology, the proposed configuration reduces harmonic distortion and semiconductor power losses while ensuring a high power factor. Simulation and experimental results validate the effectiveness of the PWM and control strategies.